Large-scale cooperative caching and application-level multicast in multimedia content delivery networks. - Jian Ni; Tsang, Danny H.K.
The Internet and multimedia technologies have greatly changed our lives. With the increasing popularity of multimedia entertainment applications over the Internet, innovative infrastructures and technologies are needed to efficiently distribute the surging amount of multimedia contents. Content delivery networks provide an intermediate layer of infrastructure that helps to deliver the contents from content providers to a large community of geographically distributed users. Cooperative caching and application-level multicast are two technologies that can be implemented in a multimedia content delivery network for delivering on-demand and live multimedia contents respectively. This article introduces the ideas and approaches of implementing cooperative caching and application-level multicast under a hierarchical architecture to achieve large-scale multimedia content delivery.
Keywords: Internet; application-level multicast; large-scale cooperative caching; multimedia content delivery network